1990
DOI: 10.1159/000168201
|View full text |Cite
|
Sign up to set email alerts
|

Additive Antiproteinuric Effect of the NSAID Indomethacin and the ACE Inhibitor Lisinopril

Abstract: Both angiotensin-converting enzyme (ACE) inhibitors like lisinopril and nonsteroidal anti-inflammatory drugs (NSAIDs) like indomethacin have been shown to lower urinary protein excretion in renal disease. If this effect is caused by different mechanisms of action, the combination of these agents could have an additive antiproteinuric effect. We studied the effects of lisinopril and indomethacin separately and in combination in 10 patients with the nephrotic syndrome. Proteinuria was lowered from 10.5 ± 1.8 g/2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…ACEI reduce intracapillary pressure, leading to a recovery in glomerular size-selective function, which may account for their antiproteinuric and potential renoprotective effect [21,22]. A selective decrease in intraglomerular transcapillary pressure has also been shown, not related to any change in systemic blood pressure, but mainly due to ACEI-induced efferent arteriolar dilation [23,24]. Table 2 Enalapril and prednisone in nephrotic-range proteinuria -serum and urine electrophoresis Fig.…”
Section: Discussionmentioning
confidence: 99%
“…ACEI reduce intracapillary pressure, leading to a recovery in glomerular size-selective function, which may account for their antiproteinuric and potential renoprotective effect [21,22]. A selective decrease in intraglomerular transcapillary pressure has also been shown, not related to any change in systemic blood pressure, but mainly due to ACEI-induced efferent arteriolar dilation [23,24]. Table 2 Enalapril and prednisone in nephrotic-range proteinuria -serum and urine electrophoresis Fig.…”
Section: Discussionmentioning
confidence: 99%
“…It would be interesting to explore other non-RAS intervening modes of therapy directed to maximization of reduction of residual proteinuria. First, different studies demonstrated that intervention in the synthesis of prostaglandins by using NSAID has antiproteinuric properties with equal effectiveness as ACEi therapy (23,24). Because of the well-known side effects of nonselective NSAID, it would be of great interest to explore whether the relative new selective COX-2 inhibitors, for which lower rates of side effects are reported, share the antiproteinuric properties of NSAID, as discussed previously (25).…”
Section: Discussionmentioning
confidence: 98%
“…The effect on proteinuria appears related to the degree of prostaglandin E-2 (PGE-2) inhibition in the urine (40,41). Moreover, when ACE inhibitors are compared with NSAID, it is reported that there is equal reduction in urinary protein excretion (42,43). A combination of both treatments resulted even in a more potent antiproteinuric effect (43,44).…”
Section: Antiproteinuric Properties Count: Another Strategy?mentioning
confidence: 99%
“…Moreover, when ACE inhibitors are compared with NSAID, it is reported that there is equal reduction in urinary protein excretion (42,43). A combination of both treatments resulted even in a more potent antiproteinuric effect (43,44). Interestingly, Vriesendorp et al (45) reported on the renoprotective effect of indomethacin when used as an antiproteinuric tool in patients with proteinuria.…”
Section: Antiproteinuric Properties Count: Another Strategy?mentioning
confidence: 99%